A Comprehensive Survey On Cloud Computing Simulators - Oladimeji, Oladosu Oyebisi; Oyeyiola, Dasola; Oladimeji, Olayanju; Oyeyiola, Pelumi (Scientific Journal of Informatics, 2021)
Purpose: Cloud Computing is one of the upcoming technologies which has gotten the attention of many researchers and investor.  But cloud computing still faces challenges because it is not economical and impractical for research institutions and industries to set up a physical cloud for research and experiments on it (cloud computing). Due to this, the researchers have chosen to test their contributions with simulators. Therefore, the purpose of this study is to perform a survey on existing cloud simulators. Methods: These cloud simulators aid in modeling cloud application through the creation of virtual machine, data Centre, and other things which can be easily added and configured to it in order to provide stress free analysis. Result: Till this present time, many cloud simulators with various features have been proposed and available for use. Novelty: In this paper, a comprehensive study has been performed on major cloud simulators by highlighting their features, strengths, and weakness through analysis. After which comparative analysis was done on the simulation, from the study, none of the simulators have the feature to simulate mobile cloud computing issues. This study has not been published anywhere else.